2009
DOI: 10.1021/nn800786p
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Gold Nanoparticle Assemblies with the Porin MspA on Mica

Abstract: The octameric porin MspA from Mycobacterium smegmatis is sufficiently stable to form a nonmembrane-supported stand-alone porin on Mica surfaces. About 98% of all MspA octamers were found to stand upright on Mica, with their periplasmic loop regions bound to the hydrophilic Mica surface. Both, small (d = 3.7 nm) and large (d = 17 nm) gold nanoparticles bind to MspA, however in different positions: small gold nanoparticles bind within the MspA pore, whereas the large gold nanoparticles bind to the upper region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Guan et al have established the Au nanoparticles functionalized by poly-Lhistidine (PLH), a simple polypeptide with a pKa value (approximately 6.2) around the physiological pH, sensitive to pH and temperature simultaneously, and can be well recognized by the color change of the Au nanoparticles by naked eyes [266]. Basel et al have reported the octameric porin MspA from Mycobacterium smegmatis, stable to form a nonmembrane-supported stand-alone porin on mica surfaces and demonstrated that the gold nanoparticles can be positioned at different, well-defined distances from the underlying surface using the MspA pore as a template and used for electrically insulating stable proteins in combination with metal nanoparticles in nanodevices [267]. Shen and Shi have reported recent advances on the synthesis, selfassembly, and biofunctionalization of various dendrimer based organic/inorganic hybrid nanoparticles (NPs) for various biomedical applications, including protein immobilization, gene delivery, molecular diagnosis, and targeted molecular imaging of cancer [268].…”
Section: Inorganic-organic Hybrid Nanoparticles For Biosensingmentioning
confidence: 99%
“…Guan et al have established the Au nanoparticles functionalized by poly-Lhistidine (PLH), a simple polypeptide with a pKa value (approximately 6.2) around the physiological pH, sensitive to pH and temperature simultaneously, and can be well recognized by the color change of the Au nanoparticles by naked eyes [266]. Basel et al have reported the octameric porin MspA from Mycobacterium smegmatis, stable to form a nonmembrane-supported stand-alone porin on mica surfaces and demonstrated that the gold nanoparticles can be positioned at different, well-defined distances from the underlying surface using the MspA pore as a template and used for electrically insulating stable proteins in combination with metal nanoparticles in nanodevices [267]. Shen and Shi have reported recent advances on the synthesis, selfassembly, and biofunctionalization of various dendrimer based organic/inorganic hybrid nanoparticles (NPs) for various biomedical applications, including protein immobilization, gene delivery, molecular diagnosis, and targeted molecular imaging of cancer [268].…”
Section: Inorganic-organic Hybrid Nanoparticles For Biosensingmentioning
confidence: 99%
“…It forms cation-selective ion channels that show voltage gating [12]. The probably most intriguing discovery is that MspA can freely stand with its axis of symmetry perpendicular to a MICA surface without the support of a self assembled monolayer or polymer-layer [13]. A self assembled monolayer is a layer of self-positioning molecules connected to a surface.…”
Section: Introductionmentioning
confidence: 99%
“…MspA is able to reconstitute within phospholipid double layers [4] and polymer layers on surfaces [5]. Moreover, this protein can stand alone on surfaces without a supporting polymer or double layer [6]. It is capable of binding gold nanoparticles [67] and Ruthenium(II) polypyridyl complexes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this protein can stand alone on surfaces without a supporting polymer or double layer [6]. It is capable of binding gold nanoparticles [67] and Ruthenium(II) polypyridyl complexes [8]. In fact, the binding of so-called “channel blockers” near the constriction zone of MspA has been discussed as a new strategy to fight mycobacterial infections, such as tuberculosis [89].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation